2021
DOI: 10.15212/ijafr-2020-0121
|View full text |Cite
|
Sign up to set email alerts
|

Fertiliser characteristics of stored spent mushroom substrate as a sustainable source of nutrients and organic matter for tillage, grassland and agricultural soils

Abstract: Spent mushroom substrate (SMS) is an organic manure that can be used with advantage in agriculture. Under European Union (EU) (Good Agricultural Practice for Protection of Waters) Regulations, SMS cannot be applied to land over the winter months and must be stored on concrete surfaces, either covered or uncovered, to prevent nutrient-rich runoff seeping into groundwater. Spent mushroom substrate at four storage facilities, two covered and two uncovered, was analysed for physical and chemical characteristics af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The application of organic materials in the form of spent mushroom substrate and manure initially stimulated the abundance of the analyzed bacterial and fungal groups (except cellulolytic bacteria). The available literature indicates that spent mushroom substrate is a waste material rich in organic matter and various macro-and micronutrients (Becher et al, 2021;Velusami et al, 2021). Furthermore, reported that the application of spent mushroom substrate, especially in the long term, increased the organic matter content in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…The application of organic materials in the form of spent mushroom substrate and manure initially stimulated the abundance of the analyzed bacterial and fungal groups (except cellulolytic bacteria). The available literature indicates that spent mushroom substrate is a waste material rich in organic matter and various macro-and micronutrients (Becher et al, 2021;Velusami et al, 2021). Furthermore, reported that the application of spent mushroom substrate, especially in the long term, increased the organic matter content in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, Wuana and Okieimen [59] reported that Cu is added to livestock fodder as a growth promoter, which may result in an increase in its content in animal waste and in the biomass of fertilized crops. Velusami et al [60] tested the fertilizer value of mushroom substrates and showed that they are a valuable source of macro-and microelements, including Cu, for plants. The correlation coefficients indicate that the increase in Cu accumulation by cocksfoot under the influence of chicken manure, bovine manure and mushroom substrate is associated with stimulation of yield by these fertilizers, discussed in a previous paper [48].…”
Section: Discussionmentioning
confidence: 99%
“…Due to growing environmental concerns, the proper disposal and handling of excess SMS accumulation are essential. Current research has clearly indicated that, due to its high fertilizing value, agricultural application is the most efficient method for SMS recycling [7][8][9][10]. SMS is a valuable source of organic matter and nutrients that is readily available to plants [8,11,12].…”
Section: Introductionmentioning
confidence: 99%